The influence of perceived risk on food supplement consumption intention - Filho, Jeferson Mendonça Pereira; Costa, Cristiane Salomé Ribeiro; Costa, Marconi Freitas da; Siqueira, Yago Menezes de (Revista de Administração da UFSM, 2024)
Purpose: The general objective of this study was to verify the relationship between the intention to consume dietary supplements and perceived risk, broken down into perceived risk in relation to health and perceived risk in relation to product performance. Design/methodology/approach: Descriptive-quantitative research was carried out via an online survey through a structured questionnaire based on the scales of Laroche et al. (2005) and DelVecchio and Smith (2005). Data analysis was performed using multiple linear regression analysis. Of the total number of questionnaires answered, 207 were considered valid. Findings: The result of the study points to statistical significance for the research hypotheses, confirming that the lower the perceived risk associated with the purchase of dietary supplements in relation to product performance and health damage, the greater the intention of consumption by individuals in this category of product. Originality/value: The confirmation of the role of risk in the consumer’s decision process leads to the observation that this risk perception is not always based on reliable information, for example, from the guidance of nutritionists and doctors. Thus, only the presentation in the communication of the effectiveness of the product and how beneficial it can be to human health, carried out by agents without technical knowledge, may not be enough for the real risks of consuming such products to be neglected.